Experience Spillovers Across Corporate Development Activities - Zollo, Maurizio; Reuer, Jeffrey J. (Organization Science, 2010)
This study develops and tests a theory of experience spillovers across corporate development activities. In particular, we investigate the impact of prior alliance experience on the performance implications of corporate acquisitions. We start with the simple suggestion that such experience spillovers will depend on the similarity among the managerial processes characterizing these activities. The empirical evidence confirms that the more the focal acquisition is managed in ways that are typical of partnerships (e.g., with low integration or with high relational quality levels), the more positive is the effect of past alliance experience on acquisition performance. However, we also find that alliance experience can be detrimental under certain circumstances, such as when the acquisition is managed with more aggressive post-acquisition integration approaches. This paper proposes a more sophisticated model of experience spillovers that can accommodate both positive and negative experience spillover effects across complex organizational tasks.